The Book of Ṣirāṭ al-Mustaqīm by Nūr al-Dīn al-Rānirī and the Development of Taṣawwuf in Lombok - Abdul Quddus (Universitas Islam Negeri Mataram, 2019)
Al-Rānirī is the first modern Sufi figure among the Malay Muslims in the 17th century. Ṣirāṭ al-Mustaqīm is his popular book that features Sufism in the archipelago. This study looks into the influence of the book on the development of Sufism in the island of Lombok. Based on the combination of anthropological-phenomenological and textual method, this study shows that al-Rānirī emphasizes in his work Ṣirāṭ al-Mustaqīm emphasized on the importance of fiqh (Islamic jurisprudence) on the practice of taṣawwuf as a response to the doctrines of wujūdiyya burgeoning among the Muslims in Aceh. The manuscript was written in Arabic, Malay, and Jawi in the 16th and the 17th century and spread along with the arrival of merchants to the Sasaknese who travelled from Lombok to Palembang and Aceh. This work has added robust fiqh features over the practices of tariqa (Sufi order) in the island of Lombok. The teachings of Tariqa Qādiriya- Naqsyabandiyya in the island regularly studied the contents of the book, from which they learnt about wuḍū’ (Ablution) and ṣalāh (praying), which are strengthened from the perspective of taṣawwuf by drawing on the nine elements of human soul formation. This is what the prominent Islamic figures in Lombok perceive as a way of ma’rifa (knowing God) through sharia rituals.